Female offenders who commit domestic violence: Aggression characteristics and potential treatment pathways. Issue 2 (6th May 2014) - McKeown, Annette
Abstract : Purpose: – The purpose of this paper is to inform understanding of female offenders who commit domestic violence. This contentious area of research is growing and there are strong indications that men and women perpetrate similar levels of domestic violence. This has resulted in increasing interest in understanding the characteristics of such offenders as well as considering treatment pathways. Design/methodology/approach: – In this study, female prisoners ( n =92) completed a measure of psychological and physical aggression (Revised Conflict Tactics Scales, Straus et al., 1996) to explore the types of domestic violence experienced and perpetrated in most recent and previous relationships. Findings: – Results indicated high levels of psychological aggression and physical assaults both experienced and perpetrated by female offenders in current and previous relationships. Physical assaults tended to be severe and high levels of mutual violence were reported both in most recent and previous relationships. Practical implications: – The findings suggest the importance of service provision and treatment pathways for female domestic violence perpetrators. On the basis of the findings, treatment needs of such offenders are considered and potential treatment pathways are reflected upon. Originality/value: – There are little known publications exploring the prevalence and characteristics of female domestic violence perpetrators in prison. Research has also tended to focus on current relationships as opposed to considering both current and previous relationships. This paper explores these areas and will be of interest to practitioners working with this client group.